Examining the effect of the marine aquarium trade on reef fish species using the abundance biomass comparison method - Hermoso, James Stephen Q. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Overcollection of fish for the marine aquarium trade negatively impacts the biodiversity and overall health of coral reef fish communities. The extent of these negative effects is often left unchecked until considerable damage has been done. Relying on the r- and K- selection theory, the abundance biomass comparison (ABC) method can detect the degree of disturbance felt by a fish community. The W-statistic is the numerical manifestation of the ABC method, with increasingly negative values indicating increasing levels of disturbance. In this study, the impact of the marine aquarium trade on reef fish species was assessed by comparing fish communities inside and outside marine protected areas (MPAs). Species richness, abundance, and biomass data were obtained using underwater visual census in 13 municipalities within Central Visayas, Philippines. Menhinick?s diversity index and environmental variables were also investigated to provide more insights. The mean W-statistic across all transects was -0.062, indicating moderate perturbation. The degrees of disturbance observed in fish communities inside and outside MPAs were not significantly different, implying that either the MPAs were not effectively protecting aquarium fish species and/or environmental factors were a stronger source of disturbance than fish collection. Statistical tests showed that the proxy indicators used to determine the levels of pollution and sedimentation were not enough to explain differences in the degrees of disturbance between sites. More specific environmental factors need to be considered. The canonical correspondence analysis revealed that all predictor variables explained about 63% of total variance of the abundance data. However, no single variable could be used to explain most of the variance. Thus, measuring the actual physico-chemical properties of the water during underwater visual census surveys is recommended. This information can be used to determine the true sources of disturbance, and marine life conservation efforts can focus on handling these sources.